USING INSTAGRAM TO LEARN AND DEVELOP ENGLISH SKILLS: CASE STUDY @theenglishnut - Tony Wibowo; Vivia Ellysinta (Universitas Internasional Batam, 2022)
Today, the use of social media is becoming increasingly popular among students. Students can use social media to keep in touch with their friends, learn about news and current affairs, occupy their free time, find interesting content, and share opinions. The popularity of social media among students can be used as a tool for language teaching. One of the most popular social networks is Instagram. This study aims to determine the effectiveness of using Instagram to learn and develop English skills and to know its impact on students' English development skills. This research is using qualitative and quantitative approach to gather data using interview and questionnaire. Many expected to give contribution for teacher to integrated Instagram into teaching and learning process. However, a more positive perception is shown to appear that there must be intention from students themselves to be able to use Instagram as learning media effectively. The questionnaire that was conducted on in this study yielded that Instagram @theenglisnut can foster language learning. Overall, this study indicated that Instagram can be used as an effective language learning tool.